Magnetic resonance and dopamine transporter imaging for the diagnosis of Parkinson’s disease: a narrative review - Otani, Rafael Tomio Vicentini; Yamamoto, Joyce Yuri Silvestre; Nunes, Douglas Mendes; Haddad, Mônica Santoro; Parmera, Jacy Bezerra (Arquivos de Neuro-Psiquiatria, 2022)
Background: the diagnosis of Parkinson's disease (PD) can be challenging, especially in the early stages, albeit its updated and validated clinical criteria. Recent developments on neuroimaging in PD, altogether with its consolidated role of excluding secondary and other neurodegenerative causes of parkinsonism, provide more confidence in the diagnosis across the different stages of the disease. This review highlights current knowledge and major recent advances in magnetic resonance and dopamine transporter imaging in aiding PD diagnosis. Objective: This study aims to review current knowledge about the role of magnetic resonance imaging and neuroimaging of the dopamine transporter in diagnosing Parkinson's disease. Methods: We performed a non-systematic literature review through the PubMed database, using the keywords "Parkinson", “magnetic resonance imaging”, “diffusion tensor”, “diffusion-weighted”, “neuromelanin”, “nigrosome-1”, “single-photon emission computed tomography”, “dopamine transporter imaging”. The search was restricted to articles written in English, published between January 2010 and February 2022. Results: The diagnosis of Parkinson's disease remains a clinical diagnosis. However, new neuroimaging biomarkers hold promise for increased diagnostic accuracy, especially in earlier stages of the disease. Conclusion:  Future validation of new imaging biomarkers bring the expectation of an increased neuroimaging role in the diagnosis of PD in the following years.
Keywords: Parkinson Disease; Parkinsonian Disorders; Diffusion Tensor Imaging; Single Photon Emission Computed Tomography Computed Tomography; Melanins; Magnetic Resonance Imaging; Diffusion Magnetic Resonance Imaging